Ukrainian ritual on the prairies : growing a Ukrainian Canadian identity - Kononenko, Natalie O. (Montreal ; Chicago : McGill-Queen's University Press, 2023)
"While Canada is home to one of the largest Ukrainian diasporas in the world, little is known about the life and culture of Ukrainians living in the country's rural areas and their impact on Canadian traditions. Drawing on more than ten years of interviews and fieldwork, Ukrainian Ritual on the Prairies describes the culture of Ukrainian Canadians living in the prairie provinces of Alberta and Saskatchewan. Despite powerful pressure to assimilate, these Ukrainians have managed to both preserve their sense of themselves as Ukrainian and to develop a culture sensitive to the realities of prairie life, creating their own uniquely Ukrainian Canadian traditions. The Ukrainian church, an iconic though now rapidly disappearing feature of the prairie landscape, takes centre stage as an instrument for the retention of Ukrainian identity and the development of a new culture. Natalie Kononenko explores the cultural elements of Ukrainian Canadian ritual practice, with an emphasis on family traditions such as marriage, birth, death, and religious holidays. Ukrainian Ritual on the Prairies gives voice to a group of everyday people who are too often overlooked, highlighting their accomplishments and their contributions to Canadian life."--
Preface: Nationalism in the time of war -- Introduction -- The sanctuary project -- The church and Ukrainian identity -- Vernacular religion -- Ukrainian weddings on the prairies -- Birth customs and baptismal rituals -- Death and the funeral -- Cemeteries and ritual change -- The calendar year -- Outreach activities : Ukrainian culture on display -- Conclusion: From the sacred to the secular, from monumental Ukrainian churches to prairie giant monuments -- Epilogue.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 05, 2023).
eBooks on EBSCOhost
Keywords: Ukrainians -- Alberta -- Ethnic identity; Ukrainians -- Saskatchewan -- Ethnic identity; Ukrainians -- Alberta -- Social life and customs -- 21st century; Ukrainians -- Saskatchewan -- Social life and customs -- 21st century; Ukrainian Canadians -- Alberta -- Ethnic identity; Ukrainian Canadians -- Saskatchewan -- Ethnic identity; Ukrainian Canadians -- Alberta -- Social life and customs -- 21st century; Ukrainian Canadians -- Saskatchewan -- Social life and customs -- 21st century; Canadiens d'origine ukrainienne -- Identité ethnique -- Alberta; Canadiens d'origine ukrainienne -- Identité ethnique -- Saskatchewan; Canadiens d'origine ukrainienne -- Alberta -- Mœurs et coutumes -- 21e siècle.; Canadiens d'origine ukrainienne -- Saskatchewan -- Mœurs et coutumes -- 21e siècle.; Ukrainiens -- Identité ethnique -- Alberta; Ukrainiens -- Identité ethnique -- Saskatchewan; Ukrainiens -- Alberta -- Mœurs et coutumes -- 21e siècle.; Ukrainiens -- Saskatchewan -- Mœurs et coutumes -- 21e siècle.; HISTORY / Canada / Post-Confederation (1867-); Ukrainians -- Ethnic identity; Ukrainians -- Social life and customs; Alberta; Saskatchewan; 2000-2099